Portföy analizi ve bir uygulama - Aykaç, M.Bige (Fen Bilimleri Enstitüsü, 1996)
Portföy Yönetimi, menkul kıymet yatırımlarında, çeşitli fınansal varlıkları birarada kullanarak risk faktörünü azaltmayı ve yüksek verim almayı sağlayan yatırım yöntemidir. Diğer yatırım araçlarının aksine portföy yönetimi size, yatırımlarınızı kendi belirlediğiniz risk grubunda değerlendirme olanağı sağlar. Bu tez çalışmasının amacı, bir portföy analizinin nasıl yapılacağı hakkında konuya ilgi duyanlara bilgi vermektir. Tezde konuyla ilgili kavramlara ve açıklayıcı örneklere yerverilmiştir. Uygulama kısmında ise, tezde anlatılanların büyük bir kısmının programı yeralmaktadır. Birinci bölümde, portföy, portföy analizi, portföy yönetimi ile ilgili tanımlar verilmektedir. İkinci bölümde, risk konusu ele alınmıştır. Riskin tanımı, yatırımcıların riske karşı tutumları, fayda kuramı, riskin bileşenleri ve risk türleri anlatılmıştır. Üçüncü bölümde, getiri konusu ele alınmıştır. Getirinin tanımı, hesaplamaları ve risk- getiri ilişkisi belirtilmiştir. Dördüncü ve beşinci bölümlerde, sırasıyla portföy analizinde geleneksel yaklaşım ve modern yaklaşım konuları anlatılmaktadır. Portföy yönetimi olarak isimlendirilen altıncı bölümde, portföylerde hangi fınansal varlıkların hangi oranlarda yer alacağı konusunda bilgi verilmektedir. Yedinci bölümde, risksiz fınansal varlıklar ve Sermaye Pazarı Doğrusu anlatılmaktadır. Sekizinci bölümde, Fınansal Varlık Pazar Doğrusu anlatılmaktadır. Dokuzuncu bölümde, beta katsayıları konusuna değinilmektedir. Onuncu bölümde, hisse senedi ile pazar portföyü arasındaki ilişkiler ve artık varyans anlatılmaktadır. Onbirinci bölümde, Markowitz modelinde farklı olan tekli indeks modeli anlatılmaktadır. Onikinci bölümde, regresyon analizleri konusu anlatılmıştır. Onüçüncü bölümde, portföy yönetiminde Sharpe Yaklaşımı anlatılmıştır. Ondördüncü bölümde, portföy yönetiminde pratik yaklaşımlar başlığı altında, yatırımcıya portföy yönetmede yardımcı olacak "formül planları" anlatılmaktadır. Bunlar sırasıyla maliyet ortalama stratejisi, sabit değer planı, sabit oran planı ve değişken oran planıdır. Onbeşinci bölümde, portföy performansının ölçülmesi ve değerlendirilebilmesi için, ölçme kriterlerinden bahsedilmektedir. Bunlar sırasıyla, Sharpe'ın performans kriteri, Treynor'un performans kriteri, Jcnseıfin performans kriteridir. Onaltıncı bölümde, bu tezde anlatılanların çoğunun uygulama olanağını sağlayan proje anlatılmakladır.

Portfolio Management is an investment management method of stocks and bonds in which different financial assets are used at the same to decrease the risk factor and to ensure high profit. In contrary to the other investment methods, Portfolio Management ensures you the possibility of evaluating your investments in a self-determined risk group. The basic advantage is lo distribute the risk. The most important way of ensuring maximum profit to your accumulation is to widespread the risk. In order to distribute risk, the selection must be done on the base of country where investment will be made, sectors, companies and the type of investment (constant or variable return), due time must be determined and also it is necessary to stragger the purchases and sales. The basic condition is the expertness. To distribute the risk in most suitable conditions, expertness is necessary. But, only the expertness following the markets regularly, evaluating the basic and technical analysis, having the possibility of getting in lo contact with national and international markets in time, and making a decision quickly using personal knowledge accumulation, decreases the investment risks and ensures high profit to your portfolio. Instead of using single investment tool, Portfolio Management consisting more than one investment tools and distributing the risks professionally, ensures you to create a reliable portfolio for own or company accumulation. The other advantages of the Portfolio Management are as follows: possibility of choosing the desired risk group, expertness of the portfolio managers, well-developed technical equipment to get into contact with markets in time, possibility of becoming a partner of a wide portfolio pool formed by many small investors accumulation in which the risk is widespreaded. XII The other reason is that, of course, in your intensive work life, it is not possible to find time for these. In a developing economy, effects of the financial markets or the development of the financial sector can be summarised as follows: Assistance to the increment of income and welfare: This can ensure the most productive distribution of a developed financial market sources. Instead of low productive investments of the person, the sources in high productive investments, securing them by institutional investors, should be assist to the increment of national income and welfare. Term adjustment: In a developed financial environment, for persons both fund offering and benefiting from funds, alternative markets and sources appear. While fund offering persons want to use these funds in short, medium or long term, there are persons needing the short, medium or long term funds. A developed financial market ensures possibility to the adjustment of the term between two section by means of different institutions and means. Adjustment of quantity: Financial markets gather the distributed small savings in a wide-based and reliable financial pool. In this way, the funds which are not competent to the investment individually, can be combined and changed to big investments. Risk adjustment: In developed markets, there will be different financial means having difference in risk. Therefore, investors will invest their savings in a financial mean whatever they want, according to their risk preference. In a good working financial market, there must be a direct proportion between risk and return, the equivalent of the high risk should be the more return. However, it must be accepted that in high risk conditions, instead of getting high profit, high loss may be occur. Establishment of large scale firms: Establishment of active operating channels between saving flowing to the financial sector and industry sector provides the opportunity to the rise of large scale capital companies in industry sector. XIII . Competition increment: Development of financial markets will increase the competition between functions such as the financial institutions, stocks and bonds, investment consulting, management, evaluation. To do this, of course, there must be no institutional and legal difficulties restricting the competition. As the result of competition, while the chance of the determination of market interest rate according to the reel size increases, the gap between the interest rate gained by savings and the credit interest rate, in other words, the gap between profit rate of fund offering and fund usage cost, will be closed. To ensure of more balanced income distribution in the community by means of distribution of the ownership to the wide people communities: Especially the development of capital market and joining of the small investors to the industrial companies by investing to the securities, will ensure the distribution of the ownership and will provide the opportunity to the relative improvement in the income distribution by means of the returns of small savings. Taking all these factors into account, it is possible to determine the dimensions of the development of the financial markets in an economy. i ) diversity of financial means, ii ) dropping the fund transfer cost by means of term, quantity and risk adjustment, iii ) changing rate of the savings and assets to the financial means. İn Türkiye, it is possible to say that, the diversity of the financial means is comparably low, the cost fund transfer is considerably higher and percentage of savings that go to the concept of financial means remains unstable. In this thesis, "Portfolio Analysis" is discussed and the computer program that may help to the investors in the stock market developed. In the first section, the definitions of the terms related with portfolio, portfolio analysis, portfolio management and short explanations are given. Risk concept is discussed in the second section. Definition of risk, investors, attitudes to the risk, utility theory, compounds of risk and risk types are explained. XIV In the third section, return concept is given. Definition of return, calculations and risk-return relation are stated. In the fourth and fifth sections, traditional and modern approaches of portfolio analysis are discussed respectively. Section six, named as portfolio management, presents the concept of the ratio of the financial assets in the portfolio. In the seventh section, the concept of financial assets having almost no risk and price-market line is explained. In the eighth section, financial assets-market line is discussed. The concept of beta coefficients is given in section nine. In the tenth section, relation between securities and market portfolio and remnant variance are explained. In the eleventh section, a single index model which is different than the Markowitz model is presented. Regression analysis concept is given in the twelfth section. In the thirteenth section, the Sharpe approach in the portfolio management is discussed. In the fourteenth section, proposed "formula plans" that may be assistant to the investors for portfolio management is explained under the heading "Practical Approach in Portfolio Management". These are; i ) dollar-cost averaging strategy, ii ) constant dollar value plan, iii ) constant ratio plan, and iv ) variable ratio plan. XV In the fifteenth section, the criteria to measure and to evaluate the portfolio performance are presented. These are; i ) Sharpe's performance criterion, ii ) Treynor's performance criterion, iii ) Jensen's performance criterion. Lastly the sixteenth section, a computer software that is developed to ensure ihc utilization of the procedure described in this thesis is given and explained.
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1996
Keywords: Portföy analizi; Sistem analizi; Portfolio analysis; System analysis